ANALISIS BEBAN KERJA DAN KEBUTUHAN PEGAWAI PD BPR ARTHA SUKAPURA CABANG SINGAPARNA - Galih - Nugraha; Siti - Rahmawati (Admisi dan Bisnis, 2016)
PD BPR Artha Sukapura Singaparna Branchis a result of the merger BPR governmentownedTasikmalaya district to support thedevelopment and the regional economy.However, after implemented merger there areproblems regarding human resourceplanning, that is the composition of theemployees who work leading to inefficienciesand not achieving the target of lending andthe handling of non-performing loans (NPL).Planning and human resource managementcan be done through an analysis of workloadand the need for employees to know thecomposition of employees with the rightamount. This study aims to 1) analyze theworkload of employees PD BPR ArthaSukapura Singaparna Branch and 2) analyzethe needs of the number of employees in PDBPR Artha Sukapura Singaparna Branch. Themethod used is the analysis of the workloadthrough the Full Time Equivalent (FTE). Theresults of the analysis of the workload onstaff of marketing fund and account officer 2staff has a value of overload and so we needone new employees for staff of marketingfunds and one new employees for accountofficer 2 staff with the status of permanentemployee.